Study on the wave impact forces below the deck of multi-column offshore floating structures - Liew, Mei Shi. (2012)
An offshore disaster brings about severe impacts to human lives and capital investment. To avoid such unfortunate events, estimation of air gap is particularly important in designing floating structures to reduce undesirable wave impact that occurs in offshore disasters. In this Final Year Project, the objective is to investigate the impact of platform dimensional changes on platform motion and wave elevation and the air gap response of the platform. The study was carried out using computer simulation. A full study of the wave impact on offshore structures is very complicated as many factors are involved. To keep the study simple, only one geometric property of the platform is assumed to change, while keeping all other factors constant. However, that is not the case in the real world as many factors are interrelated and do contribute to the impact on platform motion and wave elevation. Hence, some of the simulation results obtained differs from theoretical knowledge. In the simulation process, a variation in 1% of column diameter, 5% in pontoon length, breadth and height was carried out separately to analyse the effects on RAO motion and wave elevation.